A capacity pricing and reservation problem under option contract in the air cargo freight industry. (August 2017) - Tao, Yi; Chew, Ek Peng; Lee, Loo Hay; Wang, Lu
Highlights: An air cargo pricing and reservation model under option contract is studied. One carrier and multiple freight forwarders are considered. A Stackelberg game model is developed. Freight forwarders' optimal pricing and reservation decisions are derived. It shows through numerical results competition reduces freight forwarders' profit. Abstract: Option contracts have been increasingly applied in the air cargo freight industry over the last several decades due to its ability to mitigate asset provider's capacity utilization risk. By entering into option contract with an air cargo carrier, freight forwarders reserve a certain amount of capacity upon signing the contract and execute the option partially or completely after the market demand is realized. In this work, we address the capacity pricing and reservation problem under option contract in the air cargo freight industry. A Stackelberg game model is established to simulate the behaviors of air cargo carrier and freight forwarders. We then respectively derive optimal pricing and reservation policy for both parties with the aim to maximize their expected profits. Numerical experiments and sensitivity analysis are subsequently conducted and managerial insights are drawn for both asset provider and freight forwarders to serve as guidelines for industry participators.